A Review On Agile Decision Making In Crisis Management - Khairuddin Yap, Mohamad Nazri; A Bakar, Ahmad Zaki; Kamalrudin, Massila; Sidek, Safiah (ISoRIS, 2014)
Agility in decision making has a potential to resolve crisis management; therefore a specific agile decision making technique should be implemented in crisis management. Crisis management requires the agility in decision making in order to resolve the crisis. The decision made has to be flexible enough so that the solution can be delivered on time. In having the decision, there are people that will contribute some suggestion, opinion, experience or knowledge. The virtual knowledge sharing is the vital part on delivering the agile decision making. This paper reviews such methods on agile decision making towards crisis management and the relation with virtual knowledge sharing.